Quality nutrition, metal content, and health risks in soy milk products using aluminum and stainless steel cookers - Budi Hariono; Feby Erawantini; Aulia Brilliantina; Mokhamad Fatoni Kurnianto; Supriyono Supriyono; Syamsiar Kautsar; Rizza Wijaya; Angga Herviona Ikhwanudin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Improper processing of soymilk, such as soybean raw materials, use of well water, and use of cooking vessels, produces soymilk that does not meet SNI standards. These conditions can contaminate soymilk with harmful metals. The purpose of this study was to measure the nutritional quality and metal content of soymilk produced using aluminum and stainless steel cooking vessels. The research was descriptive and was conducted in July 2022. Analytical tests were carried out by comparing the nutritional content in the form of total protein, fat, lactose, and solid non-fat (SNF), and analyzing the heavy metal content. The results showed that the contents of Pb, Cu, and Hg in soy milk processed with stainless steel were lower than those of aluminum, from 11,494 ppm to 2,706 ppm, 114,612 ppm to 10,211 ppm, and 0,372 ppm to 0,012 ppm, respectively. The contents of Zn and As in soymilk with stainless steel were higher than those treated with aluminum, from 884,585 ppm to 73,616 ppm and from 0,107 ppm to 0,079 ppm, respectively. Cooking water also contributed 0,055; 0,044; 0,028, and 0,156 ppm to the heavy metal content of Pb, Cu, Zn, Hg, and As, respectively. In conclusion, the use of stainless steel in soymilk processing resulted in better nutritional quality and lower heavy metal content compared to aluminum.